PERANAN AUDIT INTERNAL DAN MANAJEMEN RISIKO TERHADAP EFEKTIVITAS PENGELOLAAN KREDIT PADA PT. HOME CREDIT INDONESIA - Widodo Widodo; Donny Dharmawan, SE., MM.; Hana Lidyana (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2016)
The purpose of this research is to analyze the significance of the effect of the application of internal audits of the effectiveness of credit management, analyze the significance of the effect of risk management of credit financing to the effective management of credit, as well as to analyze the significance of mutual effect the implementation of internal audit and risk management of credit financing to the effective management of credit at PT. Home Credit Indonesia. This research is quantitative. The data used were obtained from the results of observations, interviews, as well as doing the respondent's submission of the questionnaire to the staff of the company to be an expert in materials testing on the role of internal audit, risk management, credit management at PT. Home Credit Indonesia.. Based on the research results obtained in PT. Home Credit Indonesia, there is a significant influence on the effectiveness of the implementation of internal audit in the company's credit management. Besides the risk management also has a significant influence on the risk management of credit finance company's credit management effectiveness. If simultaneously, the implementation of internal audit and risk management of credit financing influence simultaneously to the effective management of credit to the company. The need for guidance to the object being audited, especially the section related to credit management about the importance of ongoing examinations in credit management to minimize the negative action of internal and external violations ranging up to monitor the credit and collection processes currently running. Improving risk management implementation either of the implemented system and the power of HR (Human Resources) that is running especially in credit management activities. The system used must be up to date so that they can cope with the new problems that they can not be overcome by using a system slama. Besides the expertise of HR personnel, especially in analyzing the loan application also needs to be improved in order to produce a sound credit so that it can generate profits for the company PT. Home Credit Indonesia